Pengaruh Metode Latihan Drill terhadap Keterampilan Tendangan Lurus dalam Pencak Silat Mahasiswa Por PJKR FIKKM Unima - Meilany Ferenika Danes; Yuliana Sattu; Djoni A. Sunkudon (STIKES Columbia Asia Medan, 2025)
Various schools of pencak silat are the original cultural heritage of the Indonesian people known as pencak silat. Although the origin of pencak silat is not known for certain, it makes sense that pencak silat has existed in Indonesia since the beginning of human civilization. One learning strategy that emphasizes practice is the drill method. One of the learning strategies for consistent and frequent practice to master a particular skill or talent is the drill method. A person's skill level is determined by the level of expertise they have achieved in various activities that are considered skills. This occurs as a result of the widely held belief that one or more prolonged patterns of movement or behavior, such as straight kicks in pencak silat, can be referred to as talent. The next problem is that there are still some students who have difficulty in doing straight kicks using the drill training method. The method used in this research is the experimental method. In this study the sample used was half of the population taken, namely 30 students. Furthermore, the sample of this study was divided into two groups, namely the experimental group of 15 people and the control group of 15 people The research instrument used in this study was the straight kick skill test. The data analysis technique used is the t-test statistical analysis technique, before the t-test is carried out, it first begins with testing the analysis requirements, namely the data normality test and the variance homogeneity test.